Symbolism of domestic pig (sus scrofa domesticus) in karmawibhangga reliefs: Ethnozoological relevance for character education - Puspitasari, Yohana Desta; Prajoko, Setiyo; Sukmawati, Ika (JPBIO (Jurnal Pendidikan Biologi), 2026)
The domestic pig (Sus scrofa domesticus) is depicted in the Karmawibhangga reliefs of Borobudur Temple, Central Java. Despite its visual presence, scientific studies discussing its symbolic meaning from ethnozoological and character education perspectives remain limited. As a representation of culture and spirituality, the depiction of the pig carries profound philosophical significance. This study aims to examine its symbolic meaning and identify character education values within these narrative panels. Using a descriptive qualitative approach and ethnographic methods, this research involves visual documentation, literature reviews, and interviews with archaeology and zoology experts. Observations were conducted at the Borobudur Museum and Cultural Heritage site, supported by morphological analysis from relevant literature. Results indicate that pigs appear in panels 9 and 74. Morphometric analysis reveals high anatomical accuracy, with body proportion similarity reaching 92.24%. These findings confirm that the pig is not merely a decorative element but a narrative supporting component conveying character education values, including: religiosity, tolerance, discipline, curiosity, appreciation of achievement, friendliness and communicative attitude, love of peace, environmental awareness, and responsibility.